Β-Ketothioamides: efficient reagents in the synthesis of heterocycles. Issue 7 (23rd December 2014) - Guo, Wei-Si; Wen, Li-Rong; Li, Ming
Abstract : β-Ketothioamides (KTAs) are versatile building blocks for the rapid construction of various heterocyclic compounds. Abstract : β-Ketothioamides (KTAs) are versatile building blocks for the rapid construction of various heterocyclic compounds. In the past decade, a number of successful reactions based on KTAs have been developed for the construction of heterocyclic skeletons under mild conditions. This minireview focuses on the annulation reactions of KTAs with dielectrophilic or dinucleophilic reagents. Multicomponent reactions using KTAs to construct various heterocycles are also the major contents in this review.